Retrospective Analysis of the Duration of Hospitalization of Imported Patients Infected with SARS-CoV-2 in Guangzhou, 2021. Issue 1 (20th January 2023) - Xie, Zhiwei; Tang, Guofang; Li, Lu; Shi, Jingrong; Gan, Qingxin; Zheng, Xiaowen; Tang, Jingyan; Zeng, Huimin; Zhang, Chuyu; Chen, Sisi; Cui, Jianping; Lin, Zishi; et al.
Abstract: The pandemic of coronavirus disease 2019 is "not over, " in fact, the "dynamic clearing" policy for SARS-CoV-2 control and prevention in China has been firmly enforced. This study aimed to analyze the clinical symptoms and dynamic viral RNA changes in 2021 at Guangzhou Eighth People's Hospital. This study showed that 31.4% of the patients (695/2212) tested negative for viral RNA from admission to the final release from quarantine. Of all negative cases, 86.5% (601/695) remained in the hospital for no more than 5 days and were asymptomatic or mild. Among the remaining 402 patients who stayed for no more than 5 days, 76.4% (307/402) were viral RNA retest positive during the isolation stage. However, 96.4% of the peak viral RNA (296/307) was over Ct = 33 cycles during the isolation stage.